Development of a tool for evaluation of clinical teaching in Davao Medical School Foundation College of Dentistry - Dimaya, Erna H. (1995)
The behaviors of instructors which facilitate and inhibit learning in the clinical setting were identified through focus group interviews and literature review. A questionnaire was developed using students as the source of information. The results were then compared to the faculty self-assessment tool adopted from the COACH skills inventory of Dr. Gary Berthold. Five categories were used in the study. They were: professional qualities and competence, maintaining conditions for clinical learning, evaluating student performance, interpersonal relationship with students, and application of knowledge of dentistry. Results showed that based on student perceptions, the availability of instructors during clinic hours which falls under the category of professional qualities and competence ranked the highest (83.5%) facilitative behavior. This was followed by analyzing student work and giving feedback (81%). Students rated the teachers equally (80%) in their show of enthusiasm for teaching and for treating them with respect. Other behaviors considered facilitative to learning by students were: giving reasons for unacceptable work, allowing students to act independently, explaining preferences for one procedure over another, seeing to the availability of resources, recognizing one's limitations as a teacher and assisting students in dental procedures. Comparing student evaluation results with faculty self-assessment using a t-test for unmatched groups showed that there is a significant difference in both their perceptions of the three categories namely: evaluating student performance, interpersonal relationship with students and in the application of knowledge of dentistry. The larger difference was found in the last category (obtained t-value 2.76. tabled t-value 1.76). The gap must have stemmed from their different understanding of their roles as teacher and student. Teachers who were taught in the traditional manner view evaluation as judgmental in nature and tend to emphasize the importance of not making any mistakes, whereas students prefer specific feedbacks regarding their work. Teachers also feel that they should distance themselves from students and do not bother about having a friendly clinical teaching environment. The teacher response to continuous and independent learning seems to be lukewarm. The students, on the other hand, shun away from what they perceive as extra and unnecessary schoolwork. Since this is the first undertaking by the researcher, further efforts should be made to improve the instruments and replicate the study. At best, this study has accomplished the initial step toward identifying clinical teaching behaviors needed in constructing an evaluation tool for clinical teaching.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Medicine -- Study and teaching (Residency)